Comparative Analysis of Activity-Based Costing Implementation: Developed vs Developing Countries - Asri Usman; Alimuddin Alimuddin; Nurul Aulia Hidayat; Nurul Maghfirah Sultan; Muthmainnah Muthmainnah (Universitas KH. Abdul Chalim Mojokerto, 2026)
Activity-Based Costing (ABC) has been widely recognized as an innovative management accounting method designed to improve cost accuracy and managerial decision-making. However, previous studies show that its implementation varies significantly between developed and developing countries due to differences in institutional readiness and economic capacity. This research addresses the problem of uneven adoption and fragmented empirical evidence regarding ABC implementation across countries with different economic classifications. Therefore, this study aims to compare the adoption of ABC in developed and developing countries, identify the main drivers and barriers influencing its implementation, and propose suitable adaptation strategies for developing economies. Using a descriptive qualitative literature review method, this study analyzes ten peer-reviewed international articles published between 2000 and 2025, representing five developed and five developing countries. The results indicate that developed countries successfully implement ABC due to strong technological infrastructure, competent human resources, top management commitment, and competitive business environments. In contrast, developing countries face challenges such as limited information technology, high implementation costs, insufficient managerial competence, and organizational resistance to change. This study concludes that the effectiveness of ABC is highly context-dependent and influenced by institutional and economic conditions. Practically, the study suggests adaptive strategies including gradual implementation, capacity building, and policy support to enhance ABC adoption in developing countries.